Marketing Failure of Sharia Business Entity Products (Case Study: 212 Mart in Jambi City) - Salmia; Mulyadi; Haramen, Mohd.; Martaliah, Nurfitri; Dewi, Novriana (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
212 Mart has tried to compete with Alfamart and Indomaret in the Indonesian retail market. However, there are several key factors that make 212 Mart unable to compete with the two minimarkets, such as scale, location, products, branding, business sustainability, and innovation have made it face difficulties. To increase its competitiveness, 212 Mart needs to consider new strategies that focus on overcoming these weaknesses and providing unique added value for customers. With hard work and appropriate adjustments, 212 Mart still has the opportunity to compete in this competitive retail market. This research will discuss the analysis of the factors causing the ineffectiveness of marketing strategies at 212 Mart in Jambi City. This study uses a descriptive qualitative research type. The results of the SWOT Analysis of the Ineffectiveness of Sharia Business Entity Product Marketing Case study of 212 Mart in Jambi City are due to the lack of promotion and the weakness of the product which is considered more expensive compared to similar outlets. Promotion is also not carried out by management, this is due to the lack of capital available in 212 Mart management, especially those in Jambi City. The strategy to improve the marketing effectiveness of Sharia Business Entity products, a case study of 212 Mart in Jambi City, has been implemented by management and has met all four indicators. However, in its implementation, there are other elements that prevent strategic improvements due to capital constraints in operational implementation at the three 212 Mart outlets.